On the interpretation of raw fundamental frequency tracings - Thorsen, Nina (Annual Report of the Institute of Phonetics University of Copenhagen, 1977)
This paper describes a procedure with which complex raw fundamental frequency (Fo) tracings can be dissolved into their constituent components, namely 1) the intonation contour of the sentence, 2) the Fo patterns associated with stress groups, 3) Fo movements pertaining to individual segments (vowels), 4) intrinsic Fo differences between segments (vowels), and 5) coarticulatory Fo variations. The problems inherent in such a procedure are discussed as are assumptions of underlying physiological production models of and perceptual correlates to the physical signal.